Applicability of Weibull distribution in Generating Model for Evaluating Lifespan Closed Circuit Television System (CCTV) - Satawat Doungpan; Vanvisa Chatchavong; K. Janchitrapongvej (Journal of Physics Conference Series, 2023)
Abstract CCTV is an expedient tool for monitoring and investigating. Since it can record emergency and routine events in memory of the electronic circuit board. However, in the process of operating CCTV, it is necessary to carry out a sampling inspection on its lifetime to predicate its availability and reliability. According to previous literature, most of the parameter estimation methods used only one parameter estimation method, which is not sufficient for identifying two explicit parameters of Weibull distribution. Moreover, the bad parameter estimation method cannot achieve reliable analysis results. Therefore, this paper presented the four methods of estimation in both graphical and analytical methods for estimating parameters of Weibull distribution. These methods have measured the accuracy by using mean square error (MSE). In addition, the real data set confirmed that there is the Weibull distribution by using the Kolmogorov-Smirnov test. The simulation results found that the maximum likelihood method (MLM) can outperform the other estimator because it can provide a minimum MSE, there is an optimal parameter in which the shape is 4.3881 and the scale is 86.8207. Finally, the two optimal parameters are applied to real data sets of the CCTV. As a result, the optimal parameter fits with real data sets, and it can evaluate the lifespan of CCTV by using the mean time to failure (MTTF) as 6.6 years.
Keywords: Statistical Distribution Estimation and Applications; Probabilistic and Robust Engineering Design; Reliability and Maintenance Optimization